Controlled release formulation of paddy pesticides intercalated layered metal hydroxide via polysaccharide encapsulation - Sharifah Norain Mohd Sharif (2019)
This research aimed to synthesis intercalated nanocomposites of paddy pesticides forcontrolled release formulation (CRF), namely zinc/aluminiumlayered doublehydroxidequinclorac (Zn/AlLDHQC), zinc hydroxide nitratesodiumdodecylsulphatebispyribac (ZHNSDSBP) and zinc hydroxide nitratesodiumdodecylsulphateimidacloprid (ZHNSDSIC) using coprecipitation method. Surfacemodification of the nanocomposites, were then performed using carboxymethylcellulose (CMC) and chitosan coatings. The physicochemical properties, CRF andkinetic behaviour were monitored using powder Xray diffraction (PXRD),thermogravimetric analysis, Fourier transform infrared spectroscopy (FTIR), elementalanalysis, field emission scanning electron microscopy (FESEM), gas sorption analysisand ultravioletvisible spectrometer. The appearance of intercalation peaks at lower 2angle in the PXRD pattern, 15.816.7 ? (Zn/AlLDHQC), 28.228.6 ? (ZHNSDSBP) and 32.032.2 ? (ZHNSDSIC) confirmed the intercalation of pesticides in thenanocomposite, which also supported by FTIR and elemental analysis. All coatednanocomposites showed better performance in releasing pesticides, with prolongrelease time ranging from 24656083 min, compared to 14784117 min for theuncoated nanocomposites. Releasing of quinclorac and imidacloprid were governed bypseudo second order kinetic model, whereby the bispyribac was governed by pseudosecond order and parabolic diffusion kinetic models. In conclusion, the nanocompositesof paddy pesticides for CRF were successfully synthesised. The CMC and chitosancoatings obviously enhance the release behaviour of the pesticides from thenanocomposites. These synthesised nanocomposites are hopefully beneficial inovercoming the excessive usage of pesticide in paddy cultivation.